What have we learnt 50 years after the first Fontan procedure?. Issue 5 (May 2020) - Gargiulo, Gaetano D.; Bassareo, Pier P.; Careddu, Lucio; Egidy-Assenza, Gabriele; Angeli, Emanuela; Calcaterra, Giuseppe
Abstract : Abstract: The Fontan procedure is often the only definitive palliative surgical option for patients with a variety of complex CHD sharing in common, a single, dominant ventricle. In recent decades, imaging and therapeutic improvement have played a crucial role in those patients in whom many complications can hamper their life. After 50 years from the first procedure, heart transplantation remains the only definitive treatment for those with a failing Fontan circulation.